Unveiling the Green Purchase Gap: A Qualitative Investigation into Consumer Decision-Making for Sustainable Products. - Unzil Al Huda (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2025)
This study investigates the green purchase gap in consumer decision-making for sustainable fashion products, with a specific focus on micro, small, and medium enterprises (MSMEs) engaged in ecoprint and thrifting businesses in East Java, Indonesia. The increasing public awareness of environmental sustainability has encouraged the growth of sustainable fashion; however, positive attitudes toward environmentally friendly products do not always translate into actual purchasing behavior. This study aims to explore how consumers interpret sustainable fashion products and identify the factors that shape the gap between environmental concern and real purchase decisions. A qualitative approach with a case study design was employed to capture the complexity of consumer experiences and considerations in a specific socio-economic context. Data were collected through in-depth interviews, observations, and documentation, and analyzed using data condensation, data display, and conclusion drawing/verification. The findings reveal that the green purchase gap is influenced not by the absence of environmental awareness, but by the interaction between sustainability values and practical consumption considerations, including price, product quality, hygiene, style compatibility, perceived risk, and trust in sustainability claims. Consumers tend to support sustainable fashion at the attitudinal level, yet actual purchasing decisions remain contingent upon whether such products are perceived as relevant, credible, and valuable in everyday consumption. Theoretically, this study contributes to the literature on sustainable consumer behavior by offering an interpretive and contextual understanding of the attitude–behavior gap in sustainable fashion consumption. Practically, the findings suggest that MSMEs should strengthen transparent communication, product storytelling, quality assurance, and value-based marketing strategies to reduce consumer hesitation and enhance actual purchase behavior. This study is limited to sustainable fashion MSMEs in East Java and the consumer perspective; therefore, future research is encouraged to expand to other sectors, regions, and methodological approaches for broader generalization.